The impact of logistics sector on sustainable development - Šulskytė, Deimantė (Vilnius University Open Series, 2019)
In the context of global economy, logistics activities are necessary for ensuring the global competitiveness of other sectors and comprehensive development of the country. In the recent years, the concept of sustainable development is changing the meaning of economic growth. Taking into account the meaning of logistics and principles of sustainable development, the main aim of the article is to assess the impact of the logistics sector on sustainable development. In order to achieve this aim, theoretical concepts of sustainable development, logistics and its relationship are revealed , as well as key macroeconomic indicators and indices are identified and applied when evaluating the impact of logistics sector on sustainable development. The findings indicate that in the context of European Union countries, logistics sectors related with transport and IT factors significantly influence different indices of sustainable development.